Pendampingan Kelompok Wanita Program Keluarga Harapan (PKH) Craft “Wanita Mandiri” di Kecamatan Sukarame Bandar Lampung - Zulfa Emalia; Ida Budiarty; Arivina Ratih (Jurnal Nusantara Mengabdi, 2021)
Purpose: The purpose of this community service activity is to assist and foster Kelompok Usaha Bersama (KUBE) Wanita Mandiri Craft which is a recipient of the Program Keluarga Harapan (PKH) assistance. This KUBE has a business of making flower crafts made from tapis. The most priority problem is that partners do not yet have the ability to prepare business feasibility studies. In addition, they do not yet have and build a partnership network by utilizing information technology including social media effectively to promote and market their products. The stages of the activities carried out consist of the preparation, implementation, mentoring, and evaluation stages. Method: The methods used are lecture and question and answer methods, demonstration methods, and non-formal discussion methods. Results: The result was, during the training activity, the participants followed it with great attention and enthusiasm until all the material had been given by the presenter which was then followed by a question and answer activity. Conclusion: All participants can take part in the entire training process from start to finish, besides that the target for delivering training materials is also achieved because the material can be delivered in its entirety and the enthusiasm of participants in participating in the training greatly supports this activity